2015
DOI: 10.1117/12.2082919
|View full text |Cite
|
Sign up to set email alerts
|

High power laser beam melting of Ti6Al4V on formed sheet metal to achieve hybrid structures

Abstract: Motivated by the desire to combine the advantages of two manufacturing concepts, namely Additive Manufacturing and sheet metal forming, the concept of hybrid processes emerged. Laser Beam Melting process with its characteristic layer by layer fabrication methodology has already been proved to be successful in fabricating fully dense 3D structures with micro sized Ti-6Al-4V powder. The presented research focuses on direct fabrication of Ti-6Al-4V Additive Structures on a thin pre-formed Ti-6Al-4V sheet metal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Hybrid components, which are manufactured using a combination of conventional processes and an AM one, can benefit from the flexibility of AM without raising the manufacturing cost commonly associated with its low deposition rate. For instance, Ahuja et al [6] showed the potential of hybrid manufacturing using laser beam melting and sheet forming to manufacture Ti6Al4V demonstrators. Additionally, Merklein et al [7] demonstrated the possibility of combining several conventional processes with AM to produce functional gear components.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid components, which are manufactured using a combination of conventional processes and an AM one, can benefit from the flexibility of AM without raising the manufacturing cost commonly associated with its low deposition rate. For instance, Ahuja et al [6] showed the potential of hybrid manufacturing using laser beam melting and sheet forming to manufacture Ti6Al4V demonstrators. Additionally, Merklein et al [7] demonstrated the possibility of combining several conventional processes with AM to produce functional gear components.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Hybrid AMconventional manufacturing processes are emerging as a viable way to overcome the build limitations of AM, thus enhancing the functionally and expanding reach of the AM technology [18,19]. Hybrid manufacturing processes pose a significant technological advance, allowing for component repairs [20][21][22][23], production of bimaterials [24][25][26][27][28], and manufacturing of large components with intricate designs [29][30][31][32][33]. Hybrid manufacturing techniques, consisting of both powder bed fusion and wire arc AM hold a promise to result in a manufacturing method which marks the benefits of both worlds, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…3), molds can be produced by alternating printing and machining operations (Fig. 4), features can be printed on top of formed components [14], and components can be embedded within printed parts ( Fig. 5 and Fig.…”
Section: Additive Manufacturing Processes and Physical Workflowmentioning
confidence: 99%